Dziecięce zabawki świąteczne w świetle wybranych źródeł ikonograficznych 2. połowy XIX i początku XX wieku - Kabacińska-Łuczak, Katarzyna; Nawrot-Borowska, Monika (Studia Edukacyjne, 2020)
The aim of this study is the reconstruction of children’s toys received by them during the Christmas period in the second half of the 19th and at the beginning of the 20th century. In its subject matter, the article refers, on the one hand, to the deliberations about Christmas toys and, on the other hand, it is part of the ever-growing trend of research on children’s toys from the historical and pedagogical perspective. The text is part of the triptych prepared by the authors on the subject of children’s Christmas toys during the period of Partitions of Poland. Selected iconographic sources – press graphics, Christmas postcards and photographs on which children’s toys can be found, comprise the source basis of this part. They are sources important for cognitive reasons, because they show the image of toys of the time, their appearance, shape, size, the way they were made, decorated, etc. They also indicate which toys were particularly popular (fashionable) and liked by children in the analysed period, and show the ways they were used.